PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Reni Setyaningsih; Haryanto Haryanto; Nelly Rhosyida (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Critical thinking skill is important to be developed in students as this skill has an important role in understanding problems. Critical thinking skills can be improved through the Realistic Mathematics Education (RME) approach as it prioritizes the process of doing mathematics in learning so that students can find mathematical concepts to solve a problem. This study aims to examine the positive effect of the RME approach on the critical thinking skill of Elementary School Teacher Education (PGSD) students at Universitas Sarjanawiyata Tamansiswa (UST). This quasi-experimental study used the pretest-posttest control group design. It involved 76 students from the PGSD study program at Universitas Sarjanawiyata Tamansiswa as samples. The number of samples was determined using the cluster random sampling technique. The data were collected by a critical thinking skills test with a total of five pre-test questions and five post-test questions. Then, the data were analyzed using the t-test to test the hypothesis. This study revealed that there is a positive effect of the RME approach on students' critical thinking skills with a significance level of 0.001 < 0.05 which indicates that H0 is rejected so that Ha is accepted.